Assessing Performance of Kerman Province`s Hospitals Using Pabon Lasso Diagram between 2008 and 2010 - M Mehrolhasani; V Yazdi Feyzabadi; T Barfeh Shahrbabak (Tehran University of Medical Sciences, 2014)
Background: A method of performance assessment is required to improve Productivity and reduce hospital costs . Pabon Lasso diagram is known as a tool for performance assessment. The current study is aimed to assess and compare Kerman province`s hospitals performance by using Pabon Lasso diagram. Materials & Methods: This descriptive and cross-sectional study was conducted retrospectively between 2008 and 2010. All hospitals of Kerman province in three groups of public, social security and private were selected by census method (N=23). The data were gathered from statistics unit and entered into SPSS 18.0. Three indicators include bed occupancy rate, bed turnover and average of length of stay were calculated and then hospitals` performance were analyzed by Pabon Lasso diagram. Results: In first two years, seven and eight hospitals out of twenty-three and in third year nine hospitals out of twenty-two located in third zone of the model (desired productivity) respectively. Among all hospitals, regarding number and ownership type, social security hospitals had better performance in 2008. Additionally Public hospitals had better performance than others in 2009 and 2010,. Conclusion: Public hospitals had better performance.Although studied hospitals` performance experienced growing trend, only one third of the them had desired performance. It can be caused by changing the provided services type from inpatient to outpatient services.It seems that Considering type of ownership and assessing past trend of 3 studied indicators concurrently is necessary for Planning for development of a broader range of inpatient services and diversified medical services based on province`s need.